2010
DOI: 10.7224/1537-2073-12.4.168
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Screening in People with Multiple Sclerosis

Abstract: Comprehensive care of people with multiple sclerosis (MS) may be jeopardized by barriers to the receipt of preventive health care by this population. The objectives of this pilot study were to estimate adherence to age-and gender-appropriate U.S. Preventive Services Task Force (USPSTF) screening recommendations in MS patients and to determine the effects of demographic characteristics on screening. In this cross-sectional study, 75 women and 9 men with an average age of 47.2 years completed a survey adapted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(42 reference statements)
1
3
0
Order By: Relevance
“…Health-care access was ascertained using patient-reported information through completion of surveys by patients in private and academic MS centers. 10 It is reassuring that their observations were generally comparable with the present data.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Health-care access was ascertained using patient-reported information through completion of surveys by patients in private and academic MS centers. 10 It is reassuring that their observations were generally comparable with the present data.…”
Section: Discussionsupporting
confidence: 80%
“…This is consistent with other literature identifying many barriers to preventive care among disabled women, most of which are based on challenges associated with accessibility. 10,18 For example, a recent study looking at barriers and facilitators related to breast cancer screening in patients with MS reported that more than 80% of women who have not received annual mammograms had mobility impairment. 19 These patients were also more likely to report additional barriers to screening, such as transportation issues, inaccessibility within the facility, difficulty with positioning in the mammogram machine, and barriers related to health-care providers, such as negative attitudes and a lack of referrals.…”
Section: Discussionmentioning
confidence: 99%
“…Managed care may also be able to use these findings to identify patients who may benefit from interventions. Some patients with MS may not be receiving the recommended preventive care services, 28 and some of the comorbid conditions prevalent in patients with MS may be prevented with proper screenings or better managed with additional patient counseling. 29 Care of patients with MS is optimized with a comprehensive care approach, 30 and the increased complexity from comorbidities reinforces the importance of integrated care.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer Ensure appropriate cancer screening per guidelines, e.g., mammogram, cervical cancer screening, colonoscopy (95). Women with disabilities, including MS, are less likely to get screening (possibly due to clinician biases and more burdensome medical care) (70).…”
Section: Comprehensive Carementioning
confidence: 99%